THE METHODS OF CHOLEDOCHOLITHIASIS TREATMENT - N. V. Merzlikin; V. F. Podgornov; Ye. V. Semichev; P. S. Bushlanov; V. D. Talacheva (Бюллетень сибирской медицины, 2015)
The methods of choledocholithiasis treatment, which are currently used in clinics of the Russian Federa-tion, has been presented. The problems of diagnosis and treatment of gallstones (GSD) in individuals of different age groups are spotlighted. In the study of treatment of cholelithiasis and choledocholithiasis, including arising complications, it can be concluded that so far the ideal method of treatment of this pa-thology has not been found. Up to now, the majority of doctor’s main treatment is surgical removal of gall stones by some method or other.This article also considers a conservative approach (drug: antispasmodics (selective and nonselective), and non-pharmacological: treatment, diet), describes the criteria and assessment of the effectiveness of therapeutic interventions that help in the question of further treatment: the continuation of drug therapy or assignment of surgical treatment. Invasive techniques that are covered in the article, namely, a tech-nique of remote and endoscopic lithotripsy, are high-tech and in demand at the moment, which, along with high efficiency removal of a stone, reduced the number and severity of postoperative complications. Additionally, in the analysis of the features of a particular method of treatment, advantages and disadvantages of different treatment methods are described, indications and contraindications (absolute and relative) together with complications, possible outcomes, and further prognosis are high-lighted.